Effect of covid-19 pandemic on saving and investment habits of individuals in kurnool town, andhra pradesh - Thouseef Ahamed; K, Venugopal Rao (Journal of Management and Science, 2021)
Worldwide Covid 19 has affected millions of peoples life. It caused not only a health crisis, but also cause the global economy to suffer. Nationwide lockdown has left the general population in an adverse state affecting their businesses and jobs on a great scale. Saving and investment has once again evolved as important pillars of our economy to support our country to survive in this current pandemic situation. In India saving is a deep rooted habit which helped our country in many global economic crises. The aim of this article is to analyze the impact of Covid 19 on saving and investment habits of the people in Kurnool, Andhra Pradesh region.